Comparative study of therapy‐related and de novo adult b‐cell acute lymphoblastic leukaemia. (25th October 2021) - Abdel Rahman, Zaid H.; Parrondo, Ricardo D.; Heckman, Michael G.; Wieczorek, Mikolaj; Miller, Kevin C.; Alkhateeb, Hassan; Sproat, Lisa Z.; Murthy, Hemant; Hogan, William J.; Kharfan‐Dabaja, Mohamed A.; Peterson, Jess F.; Baughn, Linda B.; et al.
Summary: We report a comparative analysis of patients with therapy‐related acute lymphoblastic leukaemia (tr‐ALL) vs de novo ALL. We identified 331 patients with B‐ALL; 69 (21%) were classified as tr‐ALL. The most common prior malignancies were breast (23·2%) and plasma cell disorders (20·3%). Patients with tr‐ALL were older (median 63·2 vs. 46·2 years, P  < 0.001), more often female (66·7% vs. 43·5%, P  < 0·001), and more likely to have hypodiploid cytogenetics (18·8% vs. 5·0%, P  < 0·001). In multivariable analysis, patients with tr‐ALL were less likely to achieve complete remission [odds ratio (OR) = 0·16, P  < 0·001] and more likely to be minimal residual disease‐positive (OR = 4·86, P  = 0·01) but had similar OS after diagnosis and allo‐haematopoietic cell transplantation.